The impact of vocational education on poverty reduction, quality assurance and mobility on regional labour markets - selected EU-funded schemes - Wallenborn, Manfred [Verfasser] (My University, 2009)
"Vocational education can serve to promote social stability and sustainable economic and social development. The European Union (EU) strategically employs a range of vocational educational schemes to attain these overriding goals. Topical points of focus are selected in line with requirements in the individual partner countries or regions. However, during scheme planning and implementation, flexible and problem-oriented approaches by which partners retain responsibility, while also having the opportunity to participate in learning processes, are of equal importance. This approach produces realistic assessments of the possible effects of interventions in the form of international cooperation. Flexible procedures and fixed-term schemes subject to limited financial input provide a vital basis for such learning processes, which improve partners' capacity to act in preparation for far-reaching political decisions with regard to innovative changes and fundamental reforms in qualification systems. " (Autorenreferat, BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; S 2.3 Berufsbildungspolitik; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; G 2.4 Sozialer Wandel; G 1.3.3.3 Mobilität; I 2.2 Europa; Berufsbildung; Regionaler Arbeitsmarkt; EU-Bildungspolitik; EU-Programm; Internationale Zusammenarbeit; Armutsbekämpfung; Berufliche Mobilität; Europa